Intricate Thicket : Reading Late Modernist Poetries - Scroggins, Mark, 1964- (Book collections on Project MUSE., 2015)
"This project gathers essays on a wide range of key twentieth and twenty-first century poets and writers. Scroggins examines the legacy of Louis Zukofsky (the subject of his two earlier books with the University of Alabama Press), assesses the extraordinarily influential Black Mountain poets, and provides close readings of individual books and detailed career overviews of a number of the most dynamic, innovative, and celebrated poets of the past half-century, among them Ian Hamilton Finlay, Ronald Johnson, Rae Armantrout, Harryette Mullen, Anne Carson, and others. Taken together these essays make a cumulative argument for the persistent vitality of the modernist tradition in contemporary writing, and for the intellectual and aesthetic richness made available by modernist techniques of composition. These essays are rich with detail and careful close interpretation, and are written in a lively, accessible style. While Scroggins does not shy away from engaging with complex and challenging works, his writing is pitched towards an interested, educated readership, and steers clear of theoretical entanglements and specialized jargon. And while interpreting poems is at the center of these essays, Scroggins does not hesitate to make aesthetic judgments about the successes or failures of particular texts. He situates his own critical practice and his own aesthetic investments in a concluding pair of essays, one of them a consideration of the practical and theoretical challenges of literary biography (with special reference to his work on the critically acclaimed The Poem of a Life: A Biography of Louis Zukofsky) and the other a reflection on his own aesthetics as a publishing poet"--